Analysis of Applicator Insertion Related Acute Side Effects for Cervical Cancer Treated With Brachytherapy - Chen, Jiajun; Zhang, Ning; Liu, Ying; Han, Dongmei; Mao, Zhuang; Yang, Wei; Cheng, Guanghui (Frontiers in Oncology, 2021)
Purpose: To report applicator insertion related acute side effects during brachytherapy (BT) procedure for cervical cancer patients. Materials and Methods: Between November 2017 and December 2019, 407 BT fractions were performed in 125 patients with locally advanced cervical cancer. Acute side effects recorded comprised anesthesia-related side effects, mechanical-related side effects and infection, whose frequency and degree were recorded. Pain was assessed using numeric rating scale, vaginal bleeding volume was counted by weighing gauze pieces used in packing. The BT procedure comprised eight stages: anesthesia, applicator insertion, image acquisition, transport, waiting for treatment, dose delivery, applicator removal and removed which denoted 0.5-12.0 hour period after removal, with time of each stage recorded. Factors influencing acute side effects were assessed by Spearman correlation and Mann-Whitney U test. Results: The most common acute side effect was pain, followed by vaginal bleeding. The mean scores for pain were highest during removal time, 4.9 ± 1.6 points. The mean vaginal bleeding volume was 44.4 ml during removal time. Mean total procedure time was 218.8 (175-336) minutes, having positive relationship with frequency of acute side effects. The total procedure time with acute side effects was longer than that without acute side effects. The longest procedure time was waiting time, 113.0 (91.0-132.0) minutes. More needles generated higher pain scores and larger volume of vaginal bleeding. Conclusion: Pain and vaginal bleeding were the most common acute side effects, especially during removal time, which physicians should focus on. Shortening patients' waiting time helps to reduce the total procedure time, thus, reduce acute side effects. While meeting dose requirement, less needles is helpful to reduce acute side effects.